(untitled) (Research, Society and Development, 2021)
The birth process has always been seen as one of the most special moments in a woman’s life. However, situations of obstetric violence during the pregnancy and puerperal period are very present in public and private institutions, causing a painful event both physically and psychologically. Thus, this article aimed to describe obstetric violence and its implications for the well-being of parturients and to investigate the current scientific production on the subject, and demonstrate methods that enable the quality of care. The study consists of an integrative literature review with a theoretical approach. 43 articles were initially selected that addressed the descriptors, which after analyzing the object of study and the inclusion criteria, remained 21 articles, in the language: Portuguese, published between 2014 and 2020. The exclusion criteria were thesis publications, dissertation, monograph and duplicate materials and articles not directly related to the research theme. Women have the right to choose obstetric care, therefore, they must have their dignity assured with regard to the basic principles of sexual and reproductive rights. Changes in current obstetric care practices are considered necessary, in order to reduce unnecessary interventions, and to promote actions of humanization of care.